Four Opportunities To Revitalize The US Biomedical Research Enterprise - Reece, E Albert; Balser, Jeffrey R; Bibbins-Domingo, Kirsten; Fraser, Claire M; Fried, Linda P; Kurth, Ann; Parikh, Sudip; Rutta, Randall L; Woolley, Mary; Yamamoto, Keith R; Zerhouni, Elias; Zoghbi, Huda Y; et al. (Health affairs (Millwood, Va.), 2025)
The US biomedical research enterprise is renowned for its historical and ongoing scientific breakthroughs and advancements. Yet its capacity to solve complex health issues, bridge health equity gaps, and strengthen public trust is constrained by the lack of an overarching national vision, fragmented coordination for research funding, and critical workforce recruitment and retention challenges. To improve national health outcomes and retain global competitiveness, the sector must embrace new approaches. This article, part of the National Academy of Medicine's Vital Directions for Health and Health Care: Priorities for 2025 initiative, identifies four key opportunities to revitalize the biomedical research enterprise: establishing a national advisory body, bolstering the workforce, prioritizing research to reduce health disparities, and developing approaches to streamlining and coordinating federal research funding. These priorities will help the biomedical research enterprise meet twenty-first-century challenges, promote healthy longevity, and preserve US leadership in the global arena.